Fenomena Menonton Drama Korea Pada Kalangan Wanita Karier (Studi Fenomenologi Pada Kalangan Wanita Karier Di Kota Karawang) - Maria, Dinda; Poerana, Ana Fitriana; Ramdhani, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
Korean culture is developing throughout the world, including Indonesia. The spread of Korean culture in Indonesia began in 2002 by airing spectacles, one of which was Korean Dramas or K-Dramas. Korean dramas are one of the shows that are widely liked by many people, both teenagers and adults. Career women are women who are involved in the professional world both in the fields of education, economy, social and others. Nowadays, many women choose dual roles, and watching Korean dramas is one of the me time for career women, some of the reasons are the influence of the surrounding environment, as entertainment, and light storylines. Therefore, the subjects selected in this study were career women. The purpose of this study is to analyze and describe how the phenomenon of watching Korean dramas among career women. This research was also conducted to prove how the daily behavior of career women, analyzed using qualitative research methods with a Phenomenological approach. The theory used is the phenomenological theory of Alfred Schutz. The data obtained in this study were collected using interview, observation and documentation techniques, then the data was analyzed using a data analysis model, namely data reduction, data presentation, drawing conclusions and verification. So that from this process it is known what the motives, meanings and daily behaviors of career women who watch Korean dramas are.